Language Interaction in Galician Electronic Writing. A Sociolinguistic and Pragmatic Approach - Mosquera Castro, Estefanía (Madrygal. Revista de Estudios Gallegos, 2015)
Electronic writing is now a highly successful graphical mode which has been studied by Linguistics in the last few years. However, a purely grammatical analysis and detached from the social environment in which it is used, seems insufficient to understand a phenomenon of such complexity. Consequently, we analyse its properties based on sociolinguistic constraints present in the Galician case. Thus, we examine the implications of the situation of linguistic contact and conflict between Galician and Spanish, we note the motivations of code-switching and code-mixing –which may not always match with those operating in the common language– and we observed that these practices are the result of the confluence of sociolinguistic and pragmatic factors.